Perbandingan Tingkat Spiritualitas Remaja Berdasarkan Gender dan Jurusan - Yuni Novitasari; Syamsu Yusuf; Ilfiandra Ilfiandra (Indonesian Journal of Educational Counseling, 2017)
Spirituality is a self-ability to recognize the power of the One mighty, like God. Through an understanding of spirituality, one understands the meaning itself, the meaning of life and the purpose of his life. So that the person is able to direct his self positively in any situation. Spiritual hopes can be implemented and developed in guidance and counseling in Indonesia. The research objective was to compare the level of spirituality adolescents by gender and majors. This research design surveys, with descriptive analysis techniques. Participants determined by population sampling techniques, a number of 122 adolescents (students) SMAN 1 Punggur, Lampung. Results of this research were obtained an average score of; boys r = 115.64, and the female r = 121.36. A significant level of 0.320, meaning that there is no difference. Meanwhile, the average score of 119.58 science major teens and young majors for IPS at 119.09. A significant level of 1,000 and that means there is no difference. The conclusions of the research were the level of teenage boys spiritualism relatively similar to adolescent girls, and adolescents in the spiritualism level science majors are relatively the same as the teenagers in the majors IPS. Recommendations are given is that research on the study and implementation of spiritual guidance and counseling can be developed, and teacher guidance and counseling so that this study can be considered to help develop students' independence through a spiritual approach.